Upaya Meningkatkan Kemampuan Membaca Permulaan Melalui Bingo pada Siswa MIN 4 Tebo - Nur Fatmawati; Muhammad Zaki; Laili Rahmi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study was motivated by the low beginning reading skills of first-grade students at MIN 4 Tebo, which were characterized by difficulties in recognizing letters, distinguishing similar letter shapes, and limited reading fluency. These problems were influenced by the dominance of conventional teaching methods and the lack of engaging instructional media. The aim of this study was to improve students’ beginning reading skills through the implementation of Bingo Reading media. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were first-grade students at MIN 4 Tebo. Data were collected through observation sheets of student and teacher activities, reading tests, and documentation. The results of the study showed that the implementation of Bingo Reading media improved the quality of classroom learning, particularly in increasing students’ attention, participation, and collaboration. In addition, the media supported the development of reading automaticity in recognizing letters, syllables, and simple words, which gradually enhanced students’ beginning reading skills across cycles. Therefore, it can be concluded that Bingo Reading media is an effective instructional strategy to improve beginning reading skills by creating an active, interactive, and enjoyable learning environment in elementary schools.